Club cell-derived brain-derived neurotrophic factor regulates murine airway mechanics and mucin production in response to IL-13 in a sex-dependent manner - Fagan, Amy; Sponchiado, Mariana; Mata, Luz; Amin, Shanil; Aguirre, J. Ignacio; Prabhakaran, Sreekala; Reznikov, Leah R. (Frontiers in Physiology, 2025)
IntroductionBrain-derived neurotrophic factor (BDNF) is a neural plasticity molecule that is increasingly recognized for its role in airway pathophysiology, including diseases like asthma. Although many cells in the airway can produce BDNF, our understanding of epithelial-derived BDNF and its role in airway health and disease remains limited.MethodsIn the current study, we studied male and female mice with conditional loss of Bdnf in airway club cells and challenged them intranasally with saline (vehicle control) or interleukin 13 (IL-13) for 4 days. We measured pulmonary mechanics and the abundance and secretion characteristics of the major secreted mucin glycoproteins, mucin 5B (Muc5b) and mucin 5ac (Muc5ac).ResultsFemale mice with conditional loss of club cell Bdnf showed increased Muc5b protein in the airway epithelia under basal and IL-13-stimulated conditions compared to female mice with intact Bdnf. In contrast, conditional loss of club cell Bdnf in male mice augmented whole-lung Muc5ac mRNA levels under basal and IL-13-stimulated conditions. IL-13-treated female mice with conditional loss of club cell Bdnf showed decreased airway elastance in response to increasing concentrations of nebulized methacholine, suggesting that loss of club cell Bdnf had a protective effect. No statistically significant differences were observed in pulmonary mechanics between male mice with or without conditional loss of epithelial cell Bdnf, although treatment effects of IL-13 were noted. Mechanistic and complementary studies performed in NCI-H322 cells, a human cell line with “club cell-like” characteristics, failed to demonstrate a relationship among BDNF, IL-13 signaling, and Muc5ac at the mRNA level.ConclusionThese data highlight sex-dependent differences and club cell-specific effects of Bdnf in regulating airway physiology under inflammatory conditions in mice, suggesting that further studies are needed to understand potential translational implications.